THE EFFECT OF CORRUPTION, ECONOMIC GROWTH AND INFLATION ON POVERTY IN SOUTH SULAWESI PROVINCE - Ade Lilis; I Ketut Patra; Ahmad Refki Saputra (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The purpose of this study is to analyze how poverty in South Sulawesi Province is influenced by corruption, economic growth, and inflation between 2020 and 2024. Methods: This study uses associative techniques and is quantitative in nature. Time series data (2020-2024) and cross-sectional data (24 districts/cities in South Sulawesi Province) are combined to form secondary data in the form of panel data. The data was obtained from the Central Statistics Agency (BPS) and related organizations. Data analysis was performed using multiple linear regression methods with a panel data model through IBM SPSS Statistics 2024 software. Results: The results show that, partially, the corruption variable has no effect on poverty in South Sulawesi Province. Meanwhile, economic growth hurts poverty, which means that poverty rates can be reduced through higher economic growth, while inflation has a positive effect on poverty, indicating that rising inflation tends to increase the number of poor people. Simultaneously, these three variables affect poverty with a contribution of 6.9%, while the remaining 93.1% is influenced by variables not included in the research model. Keywords: Corruption, Economic Growth, Inflation, Panel Data, Poverty.